Pharmacological Treatment of Functional Dyspepsia: An Old Story Revisited or a New Story to Be Told? A Clinical Review - Chaves,Jéssica (2023)
Abstract Dyspepsia incorporates a set of symptoms originating from the gastroduodenal region, frequently encountered in the adult population in the Western world. Most patients with symptoms compatible with dyspepsia eventually end up, in the absence of a potential organic cause, being diagnosed with functional dyspepsia. Many have been the new insights in the pathophysiology behind functional dyspeptic symptoms, namely, hypersensitivity to acid, duodenal eosinophilia, and altered gastric emptying, among others. Since these discoveries, new therapies have been proposed. Even so, an established mechanism for functional dyspepsia is not yet a reality, which makes its treatment a clinical challenge. In this paper, we review some of the possible approaches to treat-ment, both well established and some new therapeutic targets. Recommendations about dose and time of use are also made.